Self‐Assembly and Transport Behaviour of Non‐ionic Fluorinated and Alkylated Amphiphiles for Drug Delivery. Issue 35 (16th September 2022) - Kumar, Anoop; Krishna,; Sharma, Antara; Dhankhar, Jyoti; Syeda, Saima; Shrivastava, Anju; Sharma, Sunil K.
Abstract: A newer series of AB2 typed non‐ionic amphiphiles have been synthesized using p ‐hydroxybenzoate as a central core, which is further functionalized with two hydrophilic units, i. e. D‐lactose/poly(glycerol) dendron [G2.0]/monomethoxy poly(ethyleneglycol) and a hydrophobic alkyl/fluoroalkyl moiety. The aggregation behaviour of the synthesised amphiphiles in aqueous medium was studied using fluorescence spectroscopy, dynamic light scattering (DLS) and transmission electron microscopy (TEM) and were found to form nano‐sized aggregates. The potential of these amphiphiles to act as nanocarrier was studied using model hydrophobic probe Nile red and nimodipine by recording their UV‐visible and fluorescence spectroscopic data. For comparison purpose, analogous AB type amphiphiles were also synthesized and their transport ability analysed. A study of cell viability in HeLa cells revealed that all synthesized amphiphiles are well tolerated at the concentrations studied. The immobilized hydrolase Novozym‐435 was used to release the encapsulated dye from the inner hydrophobic core of micellar structures of synthesized amphiphiles in vitro. Abstract : A newer series of non‐ionic amphiphiles have been synthesized by using p ‐hydroxybenzoate as a central core, which is further functionalized with different hydrophilic and hydrophobic units. The model hydrophobic guests were used to examine the transport and enzyme triggered release potential of nano‐sized aggregates formed by these amphiphiles in aqueous media.